A core-shell nanocatalyst for fuel cells and a method for preparing the same
Patent Information
- Application Number
- CN202610987382.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-03
AI Technical Summary
解决现有Pt-Ni基燃料电池阴极催化剂在低铂载量和长期运行条件下易发生表层Ni组分失稳流失、Pt颗粒溶解与团聚、碳载体支撑失稳以及核壳界面结合不足等问题,进而导致电化学活性面积下降、催化层结构稳定性不足和燃料电池长期耐久性变差的问题
与现有技术相比,本发明提供的燃料电池用核壳纳米催化剂采用Pt-Ni合金内核、Pt富集外壳和高石墨化炭黑载体相结合的结构设计,并通过表层选择性调整、表层补铂沉积和低温后处理的协同工艺进行构建。该技术方案针对燃料电池阴极催化剂在长期运行过程中易出现的表层Ni组分失稳、颗粒表面缺陷较多、外层保护结构连续性不足以及核壳界面结合稳定性有限等问题进行了针对性设计,有利于提高催化剂整体结构的稳定性和燃料电池长期运行过程中的性能保持能力。
Smart Images

Figure CN122532268B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell technology, specifically to a core-shell nanocatalyst for fuel cells and its preparation method. Background Technology
[0002] Fuel cells, especially proton exchange membrane fuel cells (PEMFCs), are considered an important power source for heavy-duty commercial vehicles and logistics equipment due to their fast start-up, low operating temperature, high power density, and zero emissions. Heavy-duty applications not only require high power output but also need to balance long lifespan, high operational stability, and low total lifespan cost. Therefore, the performance and durability of the cathode catalyst become key constraints in engineering. Heavy-duty conditions place even stricter demands on catalyst durability, directly impacting the total cost of ownership of the vehicle.
[0003] The slow kinetics of the oxygen reduction reaction at the PEMFC cathode limit battery efficiency and output performance. Existing technologies often employ Pt-based catalysts to enhance reaction activity, with Pt-Ni alloy catalysts attracting significant attention due to their ability to control the electronic structure of the Pt surface, reduce platinum usage, and improve initial activity. However, Pt-based alloy catalysts generally suffer from high cost, limited utilization of precious metals, and insufficient durability, particularly prominent when pursuing both low platinum loading and high performance. Under high load, frequent start-stop, dynamic operating conditions, and high temperatures, Pt-based catalyst layers are prone to failure phenomena such as Pt dissolution and redeposition, Ostwald ripening, nanoparticle agglomeration, carbon support corrosion, and particle shedding. This leads to a continuous decline in electrochemical active area, catalyst layer structural instability, and ultimately, performance degradation and shortened lifespan. For Pt-Ni alloy catalysts, in addition to the aforementioned common problems, the surface Ni layer is more prone to instability and loss in acidic cathode environments, causing reconstruction, reduced active sites, and decreased long-term stability, making it difficult to achieve both high activity and long lifespan under low platinum conditions.
[0004] While existing technologies offer improvements through alloying, Pt-rich surface treatment, or shell construction, they generally suffer from the following shortcomings: First, they tend to focus on improving initial activity while neglecting surface instability, interface defects, and shell continuity under long-term operating conditions. Second, under heavy-load durability requirements, it is difficult to simultaneously achieve low platinum loading, effective surface protection, and a stable core-shell interface. Third, some process routes are relatively crude, which can easily lead to excessive damage to the core structure or discontinuous outer layer deposition, affecting subsequent stabilization effects. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a core-shell nanocatalyst for fuel cells and its preparation method. This invention solves the problems of surface Ni component instability and loss, Pt particle dissolution and agglomeration, carbon support instability, and insufficient core-shell interface bonding in existing Pt-Ni-based fuel cell cathode catalysts under low platinum loading and long-term operating conditions. These problems lead to a decrease in electrochemical active area, insufficient catalyst layer structural stability, and deterioration of long-term fuel cell durability. The present invention constructs a Pt-Ni alloy core, a Pt-enriched shell, and a synergistic preparation process. Through selective surface control, directional platinum deposition, and low-temperature interface stabilization, it reduces the direct exposure of easily unstable Ni components, repairs and continues the outer protective structure, and improves the core-shell interface bonding stability. Thus, without significantly increasing the Pt content, it simultaneously improves the catalyst's surface stability, active area retention capacity, and long-term operating adaptability.
[0006] The technical effects described in this invention are achieved through the following technical solution: a core-shell nanocatalyst for fuel cells, comprising the following raw materials: platinum precursor, nickel precursor, highly graphitized carbon black support, surface conditioning medium, shell deposition system and dispersion medium; Preferably, the platinum precursor is selected from either chloroplatinic acid or platinum tetraamminenitrate, and more preferably chloroplatinic acid; Preferably, the nickel precursor is selected from any one of nickel nitrate, nickel acetate, and nickel chloride, and more preferably nickel nitrate; Preferably, the highly graphitized carbon black carrier has a specific surface area of 400–900 m². 2 / g, carbon black carrier with a graphitization degree of not less than 60%; Preferably, the surface conditioning medium is selected from either an aqueous solution of citric acid or an aqueous solution of acetic acid, and more preferably an aqueous solution of citric acid; Preferably, the shell deposition system is composed of a platinum precursor, a reducing agent, and deionized water; the platinum precursor in the shell deposition system is any one of chloroplatinic acid and platinum tetraamminenitrate, more preferably chloroplatinic acid; the reducing agent is any one of sodium citrate, ethylene glycol, and ascorbic acid, more preferably ascorbic acid. Preferably, the dispersion medium is a mixture of ethylene glycol and deionized water, with a volume ratio of 2 to 4:1. Preferably, another aspect of the present invention provides a method for preparing a core-shell nanocatalyst for fuel cells, specifically comprising the following steps: S1: The highly graphitized carbon black carrier is pretreated by adding 8-12 wt% dilute nitric acid to remove impurities and appropriately introduce oxygen-containing sites on the surface; then it is washed with deionized water until neutral and vacuum dried for later use. S2: Dissolve platinum precursor and nickel precursor in dispersion medium at an atomic ratio of Pt:Ni = 2 to 4:1; add the highly graphitized carbon black support pretreated in step S1, and disperse the Pt and Ni precursors uniformly adsorbed on the support surface; then remove the solvent to obtain bimetallic precursor supported material. S3: The material obtained in step S2 is placed in a nitrogen atmosphere containing 5% H2 for pre-reduction and alloying segmented heat treatment, and after the heat treatment is completed, it is cooled to room temperature under a protective atmosphere to form a material loaded with Pt-Ni alloy core particles. S4: The material with Pt-Ni alloy core particles obtained in step S3 is brought into contact with a 0.05-0.1 mol / L surface conditioning medium and surface selective adjustment treatment is carried out under mild conditions; after the treatment, the material is washed until the pH of the filtrate is 5-7, dried, and the Ni exposure ratio of the outer surface layer is reduced, while avoiding excessive damage to the internal alloy skeleton as much as possible. S5: Add the surface-adjusted particles obtained in step S4 to deionized water to redisperse them into a suspension, and introduce the reducing agent and platinum precursor from the shell deposition system into the suspension. Perform surface platinum deposition under mild treatment conditions so that Pt is preferentially deposited on the outer surface of the particles to form a Pt-enriched shell. Then separate and wash. S6: The particles separated and washed in step S5 are subjected to low-temperature post-treatment to further stabilize the continuity of the outer shell and the bonding state of the core-shell interface. S7: Wash the core-shell nanocatalyst obtained in step S6 until there is no obvious free chloride ion residue, and dry it under vacuum to obtain the core-shell nanocatalyst. Preferably, in step S1, the solid-liquid ratio of the highly graphitized carbon black carrier to dilute nitric acid is 1g:30-50mL; the pretreatment parameters are: temperature 60-80℃, time 1-3h. In step S1, impurities and unstable components on the surface of the support are removed to reduce subsequent side reactions. On the other hand, an appropriate number of anchoring points are formed on the surface of the support to improve the uniformity of dispersion and adsorption of the platinum and nickel precursors. Preferably, in step S2, the total concentration of metal ions in the dispersion medium is 10–20 mmol / L; the total mass of Pt and Ni in the platinum and nickel precursors, calculated as metal elements, accounts for 25–35 wt% of the sum of the total mass of the high-graphitized carbon black support and the total mass of Pt and Ni; the dispersion operation is to first sonicate at 200 W for 15–30 min, then stir for 3–5 h; and then remove the solvent under reduced pressure at 60–90 °C. In step S2, a uniform bimetallic precursor loading state is constructed, which provides a prerequisite for the subsequent formation of Pt-Ni alloy core particles with relatively concentrated particle size, thereby reducing the problems of excessive particle agglomeration and excessively wide size distribution. Preferably, in step S3, the segmented heat treatment operation is as follows: first, the temperature is raised to 220-260℃ at a rate of 3-5℃ / min for pre-reduction, and held for 1-2 hours; then, the temperature is raised to 520-600℃ for alloying treatment, and held for 2-4 hours; the average particle size of the Pt-Ni alloy core particles formed is 4-6nm. Preferably, in step S4, the solid-liquid ratio of the Pt-Ni alloy core particles to the surface control medium is 1g:80-150mL; the mild treatment conditions are: stirring at 300-600rpm for 1-2 hours at 40-65℃. In step S4, the Ni component with poor stability in the outermost layer of the particles is adjusted first to reduce its direct exposure and to form a surface state on the particle surface that is more conducive to subsequent shell deposition. Therefore, this step is not simply dealloying, but rather creates conditions for subsequent shell repair and stabilization. Preferably, in step S5, the specific operation of the surface platinum deposition is as follows: the particles obtained in step S4 are added to deionized water for redispersibility to prepare a suspension with a solid content of 0.5-2 g / L, and the system temperature is controlled at 50-70℃; then a reducing agent is added so that the molar ratio of the reducing agent to Pt in the platinum precursor to be deposited is 8-12:1; then a platinum precursor solution with a Pt concentration of 1-3 mmol / L is added to the suspension at a dropping time of 20-40 min, wherein the amount of platinum added is controlled at 8 mol%-15 mol% based on the molar amount of Pt in the particles obtained in step S4; after the dropping is completed, the surface platinum deposition is continued for 1-2 h to complete the surface platinum deposition and obtain particles with a Pt-enriched shell on the surface. In step S5, the surface of the particles after surface regulation is repaired by targeted platinum supplementation, sealing surface defect sites and residual exposed Ni sites, thereby improving the continuity of the outer layer and the structural stability in the subsequent acidic cathode environment; therefore, this step is not simply increasing the amount of Pt, but a targeted repair process for surface stability. Preferably, in step S6, the low-temperature post-treatment parameters are: under a nitrogen atmosphere, the temperature is increased to 220-280°C at a rate of 1-3°C / min, and the treatment lasts for 1-2 hours; In step S6, the Pt-enriched shell formed in step S5 is further densified and its interface stabilized to reduce internal defects and interface instability factors, thereby making the core-shell structure less prone to shell loosening, particle reconstruction, or rapid attenuation of protective function during subsequent use.
[0007] The beneficial effects of this invention are as follows: Compared with existing technologies, the core-shell nanocatalyst for fuel cells provided by this invention adopts a structural design combining a Pt-Ni alloy core, a Pt-enriched shell, and a highly graphitized carbon black support, and is constructed through a synergistic process of surface selective adjustment, surface platinum deposition, and low-temperature post-treatment. This technical solution addresses the problems that easily occur in fuel cell cathode catalysts during long-term operation, such as surface Ni composition instability, numerous particle surface defects, insufficient continuity of the outer protective structure, and limited stability of the core-shell interface. This design is beneficial for improving the overall stability of the catalyst structure and the performance retention capability of the fuel cell during long-term operation.
[0008] In this invention, the Pt-Ni alloy core maintains a high level of catalytic activity while reducing the amount of Pt used. The highly graphitized carbon black support provides a stable loading interface and conductive support for the Pt-Ni alloy core, which is beneficial for improving the dispersion uniformity of the active components on the support surface and reducing the tendency of particle migration, agglomeration, and detachment. By selectively adjusting the surface of the Pt-Ni alloy core particles, the less stable Ni component in the outermost layer of the particles is preferentially controlled, reducing its direct exposure and creating a surface state conducive to subsequent shell deposition.
[0009] Furthermore, this invention employs a surface platinum-added deposition process to preferentially deposit Pt on the outer surface of particles after surface conditioning, forming a continuous Pt-enriched shell. This Pt-enriched shell serves two purposes: firstly, it helps to seal defect sites and residual exposed Ni sites on the particle surface, reducing further loss of unstable surface components under acidic cathode conditions; secondly, it improves the continuity and integrity of the particle outer layer, mitigating the performance degradation of the catalyst under long-term operating conditions caused by surface reconstruction, particle coarsening, and loss of active sites.
[0010] Furthermore, this invention incorporates a low-temperature post-treatment step after platinum deposition on the surface to densify and stabilize the formed Pt-enriched shell. This low-temperature post-treatment helps reduce internal defects and instability at the core-shell interface, improving the bonding stability between the Pt-enriched shell and the Pt-Ni alloy core. This results in better interface retention and structural stability of the core-shell structure during subsequent use, further enhancing the stability of the obtained core-shell nanocatalyst under long-term operating conditions. Attached Figure Description
[0011] Figure 1 This is a comparison diagram of the initial electrochemical active area and the electrochemical active area after accelerated aging of the catalyst samples of Example 1 and Comparative Examples 1-5; Figure 2 This is a comparison chart of the electrochemical active area retention rate of catalyst samples from Example 1 and Comparative Examples 1-5; Figure 3The graph shows a comparison of the initial 0.90V mass activity and the 0.90V mass activity after accelerated aging of the catalyst samples of Example 1 and Comparative Examples 1-5. Figure 4 This is a comparison chart of the activity retention rate at 0.90V between the catalyst samples of Example 1 and Comparative Examples 1-5; Figure 5 This is a comparison chart of Ni and Pt dissolution amounts in catalyst samples from Example 1 and Comparative Examples 1-5; Figure 6 XPS full spectra of catalyst samples from Example 1 and Comparative Examples 2-4; Figure 7 High-resolution XPS fitting images of Pt 4f for catalyst samples of Example 1 and Comparative Examples 2-4; Figure 8 The image shows the Ni 2p high-resolution XPS fitting images of the catalyst samples from Example 1 and Comparative Examples 2-4. Detailed Implementation
[0012] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Unless otherwise specified, the raw materials involved in the present invention are all purchased through conventional commercial channels. Experimental methods without specific conditions are conventional methods and conditions well known in the art, or according to the conditions recommended by the instrument manufacturer.
[0013] Example 1: A core-shell nanocatalyst for fuel cells, comprising the following raw materials: platinum precursor, nickel precursor, highly graphitized carbon black support, surface conditioning medium, shell deposition system and dispersion medium; The preparation method of the core-shell nanocatalyst for fuel cells specifically includes the following steps: S1: The highly graphitized carbon black carrier was added to 10wt% dilute nitric acid at a solid-liquid ratio of 1g:40mL and pretreated at 70℃ for 2h to remove impurities and appropriately introduce oxygen-containing sites on the surface; then it was washed with deionized water until neutral and vacuum dried for later use. S2: Chloroplatinic acid and nickel nitrate were dissolved in a dispersion medium in which ethylene glycol and deionized water were mixed in a volume ratio of 3:1 at an atomic ratio of Pt:Ni = 3:1; the total concentration of metal ions in the dispersion medium was controlled to be 15 mmol / L; then the pretreated high graphitized carbon black support from step S1 was added, so that the total mass of Pt and Ni in chloroplatinic acid and nickel nitrate, calculated as metal elements, accounted for 30 wt% of the sum of the total mass of the high graphitized carbon black support and the total mass of Pt and Ni; then the mixture was ultrasonically dispersed at 200 W for 25 min, and then stirred for 4 h to allow the platinum precursor and nickel precursor to be uniformly adsorbed on the surface of the support; then the solvent was removed under reduced pressure at 75 °C to obtain the bimetallic precursor supported material; S3: The material obtained in step S2 is placed in a nitrogen atmosphere containing 5% H2. It is first heated to 240℃ at a rate of 4℃ / min for pre-reduction and held for 1.5h. Then, it is heated to 560℃ for alloying treatment and held for 3h to obtain a material loaded with Pt-Ni alloy core particles, wherein the average particle size of the Pt-Ni alloy core particles is 5nm. S4: The material with Pt-Ni alloy core particles obtained in step S3 was contacted with 0.08 mol / L citric acid aqueous solution at a solid-liquid ratio of 1 g Pt-Ni alloy core particles: 120 mL citric acid aqueous solution. The mixture was stirred at 500 rpm for 1.5 h at 55 °C. After the treatment, the mixture was washed until the pH of the filtrate was 6, dried, and the exposed Ni ratio of the outer layer was reduced, while avoiding excessive damage to the internal alloy skeleton. S5: The particles obtained in step S4 are redispersed in deionized water to prepare a suspension with a solid content of 1.2 g / L, and the system temperature is controlled at 60℃; then ascorbic acid is added so that the molar ratio of Pt in the chloroplatinic acid to be deposited is 10:1; then a platinum precursor solution with a Pt concentration of 2 mmol / L is added to the suspension at a dropping time of 30 min, wherein the amount of platinum added is controlled at 12 mol% based on the molar amount of Pt in the particles obtained in step S4; after the dropping is completed, the temperature is maintained and stirred for 1.5 h to complete the surface platinum deposition, and particles with a Pt-enriched shell on the surface are obtained, and then separated and washed; S6: The particles separated and washed in step S5 are heated to 250°C at a rate of 2°C / min under a nitrogen atmosphere and treated for 1.5h. S7: Wash the core-shell nanocatalyst obtained in step S6 until there is no obvious free chloride ion residue, and dry it under vacuum to obtain the core-shell nanocatalyst.
[0014] Example 2: A core-shell nanocatalyst for fuel cells, comprising the following raw materials: platinum precursor, nickel precursor, highly graphitized carbon black support, surface conditioning medium, shell deposition system, and dispersion medium; The preparation method of the core-shell nanocatalyst for fuel cells specifically includes the following steps: S1: Add the highly graphitized carbon black support to 12wt% dilute nitric acid at a solid-liquid ratio of 1g:30mL, pretreat at 80℃ for 1h to remove impurities and appropriately introduce oxygen-containing sites on the surface; then wash with deionized water until neutral, and vacuum dry for later use. S2: Chloroplatinic acid and nickel nitrate were dissolved in a dispersion medium in which ethylene glycol and deionized water were mixed in a volume ratio of 2:1 at an atomic ratio of Pt:Ni = 2:1; the total concentration of metal ions in the dispersion medium was controlled to be 20 mmol / L; then the pretreated high graphitized carbon black support from step S1 was added, so that the total mass of Pt and Ni in chloroplatinic acid and nickel nitrate, calculated as metal elements, accounted for 35 wt% of the sum of the total mass of the high graphitized carbon black support and the total mass of Pt and Ni; then the mixture was ultrasonically dispersed at 200 W for 30 min, and then stirred for 3 h to allow the platinum precursor and nickel precursor to be uniformly adsorbed on the surface of the support; then the solvent was removed under reduced pressure at 90 °C to obtain the bimetallic precursor supported material; S3: The material obtained in step S2 is placed in a nitrogen atmosphere containing 5% H2. It is first heated to 260℃ at a rate of 5℃ / min for pre-reduction and held for 1h. Then, it is heated to 600℃ for alloying treatment and held for 2h to obtain a material loaded with Pt-Ni alloy core particles, wherein the average particle size of the Pt-Ni alloy core particles is 6nm. S4: The material with Pt-Ni alloy core particles obtained in step S3 was contacted with 0.1 mol / L citric acid aqueous solution at a solid-liquid ratio of 1 g Pt-Ni alloy core particles: 80 mL citric acid aqueous solution. The mixture was stirred at 600 rpm for 1 h at 65 °C. After the treatment, the mixture was washed until the pH of the filtrate was 5, dried, and the exposed Ni ratio of the outer layer was reduced, while avoiding excessive damage to the internal alloy skeleton. S5: The particles obtained in step S4 are redispersed in deionized water to prepare a suspension with a solid content of 2 g / L, and the system temperature is controlled at 70℃; then ascorbic acid is added so that the molar ratio of Pt in the chloroplatinic acid to be deposited is 12:1; then a platinum precursor solution with a Pt concentration of 3 mmol / L is added to the suspension at a dropping time of 40 min, wherein the amount of platinum added is controlled at 15 mol% based on the molar amount of Pt in the particles obtained in step S4; after the dropping is completed, the temperature is maintained and stirred for 2 h to complete the surface platinum deposition, and particles with a Pt-enriched shell on the surface are obtained, and then separated and washed; S6: The particles separated and washed in step S5 are heated to 280°C at a rate of 3°C / min under a nitrogen atmosphere and treated for 1 hour. S7: Wash the core-shell nanocatalyst obtained in step S6 until there is no obvious free chloride ion residue, and dry it under vacuum to obtain the core-shell nanocatalyst.
[0015] Example 3: A core-shell nanocatalyst for fuel cells, comprising the following raw materials: platinum precursor, nickel precursor, highly graphitized carbon black support, surface conditioning medium, shell deposition system, and dispersion medium; The preparation method of the core-shell nanocatalyst for fuel cells specifically includes the following steps: S1: Add the highly graphitized carbon black support to 8wt% dilute nitric acid at a solid-liquid ratio of 1g:50mL, pretreat at 60℃ for 3h to remove impurities and appropriately introduce oxygen-containing sites on the surface; then wash with deionized water until neutral, and vacuum dry for later use. S2: Chloroplatinic acid and nickel nitrate were dissolved in a dispersion medium in which ethylene glycol and deionized water were mixed in a volume ratio of 4:1 at an atomic ratio of Pt:Ni = 4:1; the total concentration of metal ions in the dispersion medium was controlled to be 10 mmol / L; then the pretreated high graphitized carbon black support from step S1 was added, so that the total mass of Pt and Ni in chloroplatinic acid and nickel nitrate, calculated as metal elements, accounted for 25 wt% of the sum of the total mass of the high graphitized carbon black support and the total mass of Pt and Ni; then the mixture was ultrasonically dispersed at 200 W for 15 min, and then stirred for 5 h to allow the platinum precursor and nickel precursor to be uniformly adsorbed on the surface of the support; then the solvent was removed under reduced pressure at 60 °C to obtain the bimetallic precursor supported material. S3: The material obtained in step S2 is placed in a nitrogen atmosphere containing 5% H2. It is first heated to 220℃ at a rate of 3℃ / min for pre-reduction and held for 2h. Then, it is heated to 520℃ for alloying treatment and held for 4h to obtain a material loaded with Pt-Ni alloy core particles, wherein the average particle size of the Pt-Ni alloy core particles is 4nm. S4: The material with Pt-Ni alloy core particles obtained in step S3 was contacted with 0.05mol / L citric acid aqueous solution at a solid-liquid ratio of 1g Pt-Ni alloy core particles: 150mL citric acid aqueous solution. The mixture was stirred at 300rpm for 2h at 40℃. After the treatment, the mixture was washed until the pH of the filtrate was 7, dried, and the exposed Ni ratio of the outer layer was reduced, while avoiding excessive damage to the internal alloy skeleton. S5: The particles obtained in step S4 are redispersed in deionized water to prepare a suspension with a solid content of 0.5 g / L, and the system temperature is controlled at 50℃; then ascorbic acid is added so that the molar ratio of Pt in the chloroplatinic acid to be deposited is 8:1; then a platinum precursor solution with a Pt concentration of 1 mmol / L is added to the suspension at a dropping time of 20 min, wherein the amount of platinum added is controlled at 8 mol% based on the molar amount of Pt in the particles obtained in step S4; after the dropping is completed, the temperature is maintained and stirred for 1 h to complete the surface platinum deposition, and particles with a Pt-enriched shell on the surface are obtained, and then separated and washed; S6: The particles separated and washed in step S5 are heated to 220°C at a rate of 1°C / min under a nitrogen atmosphere and treated for 2 hours. S7: Wash the core-shell nanocatalyst obtained in step S6 until there is no obvious free chloride ion residue, and dry it under vacuum to obtain the core-shell nanocatalyst.
[0016] Comparative Example 1: After step S3 in Comparative Example 1, the surface selectivity adjustment in step S4, the surface platinum deposition in step S5, and the low-temperature post-treatment in step S6 were not performed. The material obtained in step S3 was directly washed and dried to obtain a Pt-Ni alloy catalyst supported on a highly graphitized carbon black support. The composition of other raw materials and process conditions were kept the same as in Example 1. This was used to investigate the synergistic effect of surface selectivity adjustment, surface platinum deposition, and low-temperature post-treatment on the surface stability, shell construction effect, and long-term performance retention of the catalyst.
[0017] Comparative Example 2: In Comparative Example 2, the selective surface adjustment treatment in step S4 is not performed. Instead, after step S3 is completed, the obtained Pt-Ni alloy core particles are directly subjected to the surface platinum deposition in step S5 and the low-temperature post-treatment in step S6. The remaining raw material composition and process conditions are consistent with those in Example 1. This is used to investigate the effects of selective surface adjustment on the control of the Ni composition of the outermost layer of the particles, the continuity of subsequent surface platinum deposition, and the stability of the core-shell structure.
[0018] Comparative Example 3: In Comparative Example 3, after step S4 is completed, the surface platinum deposition in step S5 is not performed. Instead, the material treated in step S4 is directly subjected to the low-temperature post-treatment in step S6. The remaining raw material composition and process conditions are consistent with those in Example 1. This is used to investigate the effect of surface platinum deposition on the coverage of defect sites on particle surface, the regulation of residual exposed Ni sites, and the formation of Pt enriched shell.
[0019] Comparative Example 4: In Comparative Example 4, after step S5, the low-temperature post-treatment of step S6 is not performed. Instead, the material after platinum deposition on the surface of step S5 is directly washed and dried. The composition of other raw materials and process conditions are the same as in Example 1. This is used to investigate the effects of low-temperature post-treatment on the densification of the Pt enriched shell, the stabilization of the core-shell interface, and the structural stability under long-term operation conditions.
[0020] Comparative Example 5: The highly graphitized carbon black support used in step S1 of Comparative Example 5 was replaced with a common carbon black support. The remaining raw material composition and process conditions were kept the same as in Example 1. This was used to investigate the effect of the highly graphitized carbon black support on the dispersion state of the active components, the tendency of particle migration and agglomeration, and the overall stability of the core-shell nanocatalyst.
[0021] Basic physicochemical performance tests: Based on GB / T 20042.4-2025, the metal element content and impurity content of catalyst samples from Examples 1-3 and Comparative Examples 1-5 were tested, and the test results are shown in Table 1 below.
[0022] Table 1. Physicochemical properties of catalyst samples from Examples 1-3 and Comparative Examples 1-5
[0023] Based on the results in Table 1, among Examples 1 to 3, Example 1 showed a more balanced Pt content, Ni content, total metal loading, and impurity level. This is because Example 1 achieved a better match between the precursor ratio, surface layer control intensity, platinum addition, and low-temperature post-treatment conditions, resulting in a more coordinated final component distribution. Therefore, it was more conducive to obtaining a core-shell structure that balanced activity and stability. Example 2 had the highest Pt content, Ni content, and total metal loading due to its higher precursor concentration, total metal loading, surface layer control intensity, and platinum addition. At the same time, the residual Cl was also relatively high. Therefore, it was more likely to form a structure with a thicker outer layer but not necessarily optimal surface utilization efficiency. Example 3 had the lowest Pt content, Ni content, and total metal loading, as well as the lowest residual Cl, due to its milder overall treatment conditions, lower metal loading, and lower platinum addition. Therefore, it was easier to form a thinner outer layer and exhibit a better initial dispersion state. Comparative Example 1, lacking steps S4, S5, and S6, had no controlled surface Ni and no Pt-enriched shell, resulting in low Pt content and high Ni content. Comparative Example 2, lacking step S4, had a higher degree of Ni exposure on the particle surface, leading to the highest residual Cl content after subsequent platinum deposition, indicating that the surface state affects the quality of outer layer formation. Comparative Example 3, lacking step S5, did not form a Pt-enriched shell, resulting in significantly lower Pt content and total metal loading than Example 1, but with lower residual Cl. Comparative Example 4, lacking step S6, had metal element content similar to Example 1, but slightly higher residual Cl, indicating that low-temperature post-treatment has limited impact on the basic components, and its effect is more likely reflected in subsequent shell densification and interface stabilization. Comparative Example 5, using ordinary carbon black support, resulted in a significant increase in Fe, Cu, and Na impurities, while Pt content and total metal loading were slightly lower, indicating that highly graphitized carbon black support is beneficial for reducing impurity background and improving the effective loading stability of active components.
[0024] Electrochemical active area test: 5 mg of each catalyst sample prepared in Example 1 and Comparative Examples 1-5 were weighed and added to 750 μL of deionized water, 250 μL of isopropanol, and 20 μL of 5 wt% perfluorosulfonic acid ionomer dispersion. The mixture was ultrasonically dispersed for 30 min to obtain catalyst ink. A suitable amount of catalyst ink was then drop-coated onto the surface of a glassy carbon rotating disk electrode to ensure a consistent Pt loading on each electrode group. After drying, the electrode was used as the working electrode. A platinum wire was used as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The test was conducted in a 0.1 mol / L perchloric acid solution. Before the test, the electrode was activated under nitrogen saturation at a potential range of 0.05–1.00 V with a scan rate of 50 mV / s until the CV curve stabilized. The initial electrochemical active area of each sample group was then determined using the CO stripping method. After initial electrochemical active area testing, each group of electrodes underwent accelerated aging. The aging conditions were set in a 0.1 mol / L perchloric acid solution, with square wave potential cycling between 0.6 V and 0.95 V, each potential held for 3 seconds, for a total of 10,000 cycles. After aging, the electrochemical active area of each group of samples was measured again under the same conditions. The initial electrochemical active area and the retention rate of the electrochemical active area after accelerated aging were used as evaluation indicators for each group of samples. The test results are as follows: Figure 1 and Figure 2 As shown.
[0025] based on Figure 1-2Analysis of the results showed that Example 1 had the highest initial electrochemical active area and the highest retention rate of electrochemical active area after accelerated aging. In Example 1, the Pt-Ni alloy core particle size, the degree of surface selective adjustment, the amount of platinum deposited on the surface, and the low-temperature post-treatment conditions were well-matched, resulting in a large number of usable Pt active sites on the particle surface. Simultaneously, the Pt-enriched shell was continuous and the interface was relatively stable, thus resulting in a high initial electrochemical active area and minimal loss of active area after aging. Comparative Example 1, lacking steps S4, S5, and S6, had a higher degree of Ni exposure on the particle surface and failed to form a Pt-enriched shell, resulting in a lower initial electrochemical active area. During aging, it was more prone to Ni loss, particle coarsening, and loss of active sites, leading to the lowest retention rate. Comparative Example 2, lacking step S4, had an unstable particle surface state, affecting the uniformity of subsequent platinum deposition. Therefore, both the initial electrochemical active area and retention rate were lower than in Example 1. Comparative Example 3, lacking step S5, resulted in a lack of a Pt-enriched shell on the particle surface, with more surface defect sites and residual exposed Ni sites, leading to a lower initial electrochemical active area and more significant degradation after aging. Comparative Example 4, lacking step S6, although able to form a Pt-enriched shell and achieve an initial electrochemical active area close to that of Example 1, suffered from insufficient shell density and core-shell interface stability, resulting in a significantly lower retention rate after aging compared to Example 1. Comparative Example 5, using a common carbon black support, exhibited lower dispersion of active components and lower support stability compared to highly graphitized carbon black supports, thus resulting in both a lower initial electrochemical active area and lower retention rate after aging compared to Example 1.
[0026] Oxygen Reduction (ORR) activity test: The working electrode preparation method for each group of samples was consistent with that of Experiment 1, i.e., the catalyst samples of Example 1 and Comparative Examples 1-5 were prepared into catalyst electrodes with the same Pt loading. Platinum wire was used as the counter electrode and Ag / AgCl electrode as the reference electrode. During the test, all potentials were converted to potentials relative to the reversible hydrogen electrode (RHE). In 0.1 mol / L perchloric acid solution, linear sweep voltammetry was first performed under nitrogen saturation at 1600 rpm, with a scanning potential range of 0.05–1.00 V and a scanning rate of 10 mV / s, to obtain the background current curve. Subsequently, linear sweep voltammetry was performed again under the same conditions in oxygen-saturated 0.1 mol / L perchloric acid solution, and the obtained ORR curve was subjected to background current subtraction and iR compensation. Based on this, the kinetic current of each group of samples at a potential of 0.90 V was calculated using the Koutecký-Levich equation, and the value of the kinetic current normalized to the Pt mass on the working electrode was used as the initial 0.90 V mass activity of each group of samples. After the initial oxygen reduction activity test, the samples were treated under the same accelerated aging conditions as in Experiment 1. After aging, the activity of each sample at 0.90V was measured again under the same conditions. The initial 0.90V activity and the retention rate of activity after accelerated aging were used as evaluation indicators for each sample. The test results are as follows: Figure 3 and Figure 4 As shown.
[0027] based on Figure 3-4Analysis of the results showed that Example 1 exhibited the highest initial 0.90V mass activity and the highest retention rate of mass activity after accelerated aging. This is because Example 1 had a better match between the Pt-Ni alloy core particle size, the degree of surface selective adjustment, the amount of platinum deposited on the surface, and the low-temperature post-treatment conditions. This resulted in the formation of a relatively continuous Pt-enriched shell on the particle surface while maintaining a good state of available surface active sites, thus leading to higher initial mass activity and less degradation after aging. Comparative Example 1, lacking steps S4, S5, and S6, had a higher degree of Ni exposure on the particle surface and failed to form a Pt-enriched shell, resulting in the lowest initial mass activity and the most significant decrease in activity after aging. Comparative Example 2, lacking step S4, had insufficient control over the surface Ni composition, affecting the uniformity of subsequent platinum deposition and the integrity of the shell, thus resulting in lower initial mass activity and retention rate than Example 1. Comparative Example 3, lacking step S5, had no Pt-enriched shell formed on the particle surface, resulting in more surface defect sites and residual exposed Ni sites, leading to lower initial mass activity and further accelerated degradation after aging. Comparative Example 4, lacking step S6, although having formed a Pt-enriched shell, had an initial mass activity close to that of Example 1. However, the shell's density and the core-shell interface stability were insufficient, resulting in a significant decrease in the mass activity retention rate after aging. Comparative Example 5, using a common carbon black carrier, had inferior active component dispersion, carrier stability, and impurity control compared to a highly graphitized carbon black carrier. Therefore, both its initial mass activity and the mass activity retention rate after aging were lower than those of Example 1.
[0028] Metal leaching test: The electrode preparation method for each group of samples was consistent with that in Experiment 1, and the accelerated aging conditions were the same as in Experiment 1. All tests used the same working electrode area and the same volume of electrolyte. After accelerated aging, all electrolyte used during the aging process for each group of samples was collected, along with the electrode washing solution. Nitric acid was then added for acidification and preservation, bringing the final nitric acid concentration in the sample solution to 2%. The contents of Ni and Pt in the solution were then determined using inductively coupled plasma atomic emission spectrometry (ICP-AES) or inductively coupled plasma mass spectrometry (ICP-MS). Based on the measured elemental concentrations and the total volume of the collected solution, the total leaching amount of Ni and Pt for each group of samples was calculated and normalized according to the Pt loading on the working electrode to obtain two evaluation indicators: Ni leaching amount (μg / mgPt) and Pt leaching amount (μg / mgPt). The test results are as follows: Figure 5 As shown.
[0029] based on Figure 5Analysis of the results showed that Example 1 had the lowest Ni and Pt leaching amounts. This is because the selective surface adjustment in Example 1 reduced the direct exposure of unstable Ni components on the outermost layer of the particles, and the platinum deposition on the surface further formed a Pt-enriched shell. The low-temperature post-treatment also improved the shell density and core-shell interface stability, thus effectively suppressing the loss of Ni and Pt during accelerated aging. Comparative Example 1, lacking steps S4, S5, and S6, lacked effective surface regulation and a continuous protective shell on the particle surface, resulting in the highest Ni and Pt leaching amounts. Comparative Example 2, lacking step S4, had a higher degree of Ni exposure on the particle surface, affecting the quality of subsequent platinum shell formation, thus resulting in a significantly higher Ni leaching amount than Example 1, accompanied by an increase in Pt leaching. Comparative Example 3, lacking step S5, did not form a Pt-enriched shell on the particle surface, resulting in more surface defect sites and residual exposed Ni sites, thus leading to significant Ni and Pt leaching. Comparative Example 4, lacking step S6, although a Pt-enriched shell was formed, lacked sufficient shell density and core-shell interface stabilization. Therefore, its Ni and Pt leaching amounts were higher than in Example 1 but lower than in Comparative Examples 2 and 3. Comparative Example 5, using a common carbon black support, had lower active component loading stability and support durability than highly graphitized carbon black supports. Therefore, it was more prone to particle migration and support-related instability during accelerated aging, resulting in a higher Pt leaching amount and a higher Ni leaching amount than in Example 1.
[0030] Spectral Analysis: Appropriate amounts of the catalyst powders obtained in Examples 1, 2, 3, and 4 were vacuum-dried at 60°C for 12 hours to remove adsorbed water and volatile residues from the sample surface. The dried catalyst samples were then evenly spread on the conductive adhesive or sample stage surface, gently pressed to ensure firm adhesion and a smooth surface, and subsequently placed in the sample chamber of an X-ray photoelectron spectroscopy (XPS) instrument for testing. The spectra are shown below. Figure 6-8 As shown.
[0031] based on Figure 6-8 Analysis of the corresponding results shows that XPS tests of Example 1 and Comparative Examples 2, 3, and 4 indicate that characteristic peaks of Pt 4f, C 1s, O 1s, and Ni 2p were detected on the surface of each sample, indicating that the sample surfaces all contain Pt-Ni related active components and carbon support components. As can be seen from the full spectrum, the Pt 4f characteristic peak of Example 1 is relatively stronger, while the Ni 2p characteristic peak is relatively weaker, indicating a higher degree of Pt enrichment and a lower degree of Ni exposure on its surface; the Ni 2p peak of Comparative Example 3 is the most prominent, indicating the highest degree of Ni exposure on its surface; Comparative Examples 2 and 4 are in between.
[0032] As can be seen from the high-resolution Pt 4f fitting plot, Example 1 exhibits significant Pt at approximately 71.34 eV. 0Main peak, and Pt 0 The high proportion of the component indicates that the surface metallic Pt is well preserved, and the surface Pt-enriched shell is well formed. Compared with Comparative Example 3, the Pt in Example 1... 0 The main peak shifts slightly towards higher binding energy, indicating a more pronounced electronic interaction between Pt and the Ni core. Compared to Comparative Example 4, the Pt 4f peak in Example 1 is more concentrated, indicating that the surface Pt enrichment shell and core-shell interface are more stable after low-temperature post-treatment. Comparative Example 2 lacks step S4, resulting in insufficient surface state control and relatively uneven surface Pt state after subsequent platinum deposition. Comparative Example 3 lacks step S5, leading to insufficient surface Pt enrichment, thus its Pt... 0 The signal is weak.
[0033] As can be seen from the high-resolution fitting diagram of Ni 2p, the overall signal of Ni 2p in Example 1 is the weakest, and Ni 2+ The smaller composition and satellite peak area indicate the lowest degree of direct Ni exposure on the surface, and good continuity of the surface Pt-enriched shell. In Comparative Example 3, because step S5 was not performed, no Pt-enriched shell formed on the particle surface; therefore, the Ni 2p signal was the strongest. 2+ The composition was also the most obvious; although Comparative Example 2 underwent platinum deposition, the Ni composition of the outermost layer of the particles was not sufficiently regulated due to the lack of step S4, so the Ni signal was still relatively strong; Comparative Example 4 completed steps S4 and S5, and the Ni signal was weaker than that of Comparative Example 2 and Comparative Example 3, but due to the lack of step S6, its shell densification and interface stabilization were still lower than those of Example 1.
[0034] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a core-shell nanocatalyst for fuel cells, characterized in that, Includes the following steps: S1: For surfaces with a specific surface area of 400–900 m² 2 / g of highly graphitized carbon black carrier with a graphitization degree of not less than 60% is added to 8-12wt% dilute nitric acid at a solid-liquid ratio of 1g:30-50mL, pretreated at 60-80℃ for 1-3h, then washed with deionized water until neutral, and vacuum dried for later use. S2: Dissolve platinum and nickel precursors in a dispersion medium, add the pretreated high graphitized carbon black support from step S1, and disperse the Pt and Ni precursors to uniformly adsorb onto the support surface. Then remove the solvent to obtain the bimetallic precursor-supported material. S3: The bimetallic precursor loading material obtained in step S2 is placed in a nitrogen atmosphere containing 5% H2. It is first heated to 220-260℃ at a rate of 3-5℃ / min for pre-reduction and held for 1-2 hours. Then, it is heated to 520-600℃ for alloying treatment and held for 2-4 hours. After the heat treatment, it is cooled to room temperature under a protective atmosphere to form a material loaded with Pt-Ni alloy core particles. The average particle size of the Pt-Ni alloy core particles is 4-6 nm. S4: The material with Pt-Ni alloy core particles obtained in step S3 is contacted with a 0.05-0.1 mol / L citric acid aqueous solution, wherein the solid-liquid ratio of the Pt-Ni alloy core particles to the citric acid aqueous solution is 1 g: 80-150 mL. The surface selective adjustment treatment is carried out by stirring at 300-600 rpm for 1-2 h at 40-65 °C. After the treatment, the filtrate is washed until the pH of the filtrate is 5-7 and then dried. S5: The surface-adjusted particles obtained in step S4 are added to deionized water for redispersibility to prepare a suspension with a solid content of 0.5–2 g / L, and the system temperature is controlled at 50–70 °C; then a reducing agent is added so that the molar ratio of the reducing agent to Pt in the platinum precursor to be deposited is 8–12:1; then a platinum precursor solution with a Pt concentration of 1–3 mmol / L is added to the suspension over a dropping time of 20–40 min, wherein the amount of platinum added is controlled at 8 mol%–15 mol% based on the molar amount of Pt in the particles obtained in step S4; after the dropping is completed, the mixture is kept warm and stirred for 1–2 h to complete the surface platinum deposition, so that Pt is preferentially deposited on the outer surface of the particles to form a Pt-enriched shell, and then separated and washed; S6: The particles separated and washed in step S5 are heated to 220-280℃ at a rate of 1-3℃ / min under a nitrogen atmosphere and treated for 1-2 hours. S7: Wash the core-shell nanocatalyst obtained in step S6 until there is no obvious free chloride ion residue, and dry it under vacuum to obtain the core-shell nanocatalyst for fuel cells.
2. The method for preparing a core-shell nanocatalyst for fuel cells according to claim 1, characterized in that, In step S2, the platinum precursor and the nickel precursor are dissolved in the dispersion medium at an atomic ratio of Pt:Ni = 2 to 4:1; The total concentration of metal ions in the dispersion medium is 10–20 mmol / L; the total mass of Pt and Ni in the platinum and nickel precursors, calculated as metal elements, accounts for 25–35 wt% of the sum of the total mass of the high-graphitized carbon black carrier and Pt and Ni; the dispersion operation is to first sonicate at 200W for 15–30 min, then stir for 3–5 h, and then remove the solvent under reduced pressure at 60–90 °C.
3. The method for preparing a core-shell nanocatalyst for fuel cells according to claim 2, characterized in that, In step S2, the platinum precursor is selected from chloroplatinic acid and tetraammineplatinum nitrate; the nickel precursor is selected from nickel nitrate, nickel acetate and nickel chloride; the dispersion medium is a mixture of ethylene glycol and deionized water with a volume ratio of 2 to 4:
1.
4. The method for preparing a core-shell nanocatalyst for fuel cells according to claim 3, characterized in that, In step S5, the platinum precursor is selected from either chloroplatinic acid or tetraammineplatinum nitrate; the reducing agent is selected from either sodium citrate, ethylene glycol, or ascorbic acid.
5. The method for preparing a core-shell nanocatalyst for fuel cells according to claim 4, characterized in that, In step S2, the platinum precursor is chloroplatinic acid, the nickel precursor is nickel nitrate, and the dispersion medium is a mixture of ethylene glycol and deionized water in a volume ratio of 3:1; in step S5, the platinum precursor is chloroplatinic acid, and the reducing agent is ascorbic acid.
6. A core-shell nanocatalyst for fuel cells, characterized in that, The core-shell nanocatalyst is prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Platinum-bismuth alloy catalyst, preparation method thereof and direct methanol fuel cell
CN121862772A
Fuel cell cathode catalyst and preparation method therefor, membrane electrode and fuel cell
WO2021114056A1
KR20190030387A